Hijab – muslim response to globalisation? - Kuriata, Agnieszka (Człowiek i Społeczeństwo, 2016)
Young Muslim women are coming under an increasing influence of globalisation processes and follow global trends, which also includes fashion. This entails a certain balancing act between being modern and being religious. The author of the present paper attempts to address the question whether the hijab may be considered a Muslim answer to globalisation through its presence within the so-called “hijab fashion,” or that perhaps, to the contrary, it constitutes a symbol of a growing isolation and separation of Muslim minorities inhabiting the countries of western Europe.